Research on the industrial chain network-driven innovation model of China's audio-visual industry park - CHEN, Yang (Institutional Knowledge at Singapore Management University, 2024)
This dissertation explores the model through which Chinese audio-visual industry parks drive innovation leveraging industrial chain networks, with Xing Guang Movie and Television Park as the core case study. It also integrates analyses of several other representative Chinese audio-visual industry parks. Based on these case analyses, it identifies critical elements essential for successful innovation within audio-visual industry parks driven by industrial chain networks, thereby providing a realistic foundation for the theoretical framework of the thesis. Drawing on innovation theory, network theory, industrial chain network theory, and collaborative capability theory, this study abstracts the model driving innovation through industrial chain networks into theoretical constructs: the impact of network embeddedness on innovative performance and the process by which network embeddedness enhances innovative performance through collaborative capabilities. This forms the theoretical research framework of the thesis, presenting six theoretical hypotheses for testing. To test these hypotheses, the thesis surveyed 150 companies within the Xing Guang Movie and Television Park, collecting data on companies' network embeddedness, collaborative capabilities, and innovative performance. The empirical research supports all the above six hypotheses. Finally, the thesis proposes recommendations to foster innovation within Chinese audio-visual industry parks, including developing innovation carriers, establishing industry collaboration platforms, creating industry incubation bases, and enhancing legal or policy frameworks governing corporate relationships. This thesis provides in-depth insights into the innovation model of Chinese audio-visual industry parks, offering valuable implications for enterprises, park administrators, and policymakers.